2016
DOI: 10.1007/s00134-016-4454-9
|View full text |Cite
|
Sign up to set email alerts
|

Statins in patients with sepsis and ARDS: is it over? We are not sure

Abstract: International audienceno abstrac

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…(2) Are statins more appropriate for the prevention or for the treatment of sepsis-associated ARDS [68] ? (3) What is the adequate statin and statin dose associated with better outcomes in sepsis/ARDS [71] ?…”
Section: Ards Epidemiologymentioning
confidence: 99%
“…(2) Are statins more appropriate for the prevention or for the treatment of sepsis-associated ARDS [68] ? (3) What is the adequate statin and statin dose associated with better outcomes in sepsis/ARDS [71] ?…”
Section: Ards Epidemiologymentioning
confidence: 99%
“…In these regions, circulating statins interact directly with endothelial cell layers, raising the possibility that statin inhibition of an invasion would limit the progression of endovascular infection. McAuley et al maintain that patients with underlying endovascular disease may benefit from statin therapy in an infection setting [ 37 ]. However, epidemiological and medical research using observational studies on cardiac implant infection in patient populations on a statin regimen is minimal, but at least one study suggests that statin therapy offers protection against infection.…”
Section: Settings Where Biology Suggests Statins May Offer Protection...mentioning
confidence: 99%
“…Statins, traditionally administered to lower serum cholesterol, have been considered an attractive class of drugs in the setting of COVID-19 [ 2 , 3 ] due to their pleiotropic effects, including anti-inflammatory, immunomodulatory, antithrombotic, and antimicrobial properties [ 4 , 5 ]. Previously studies have evaluated the use of statins in the treatment of pneumonia and ARDS (Acute Respiratory Distress Syndrome) [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Particularly, an analysis of 540 individuals from the HARP-2 (hydroxymethylglutaryl-CoA Reductase Inhibition with Simvastatin in Acute Lung Injury to Reduce Pulmonary Dysfunction-2) trial demonstrated improved survival upon statin treatment in patients with a hyperinflammatory phenotype [ 11 ].…”
Section: Introductionmentioning
confidence: 99%